The Application of 20 inch MCP-PMT In LHAASO-WCDA - You X. (2023)
In the Large High Altitude Air Shower Observatory (LHAASO), the main physics objective of the Water Cherenkov Detector Array (WCDA) is to survey the gamma-ray sky continuously in the energy range from 100 GeV to PeV. The Water Cherenkov detector array, covering an area of about 78,000 m2 area, is constituted by 3120 detector units divided into 3 separate arrays. In the second and third array are installed 2220 20" PMTs instead of the 8 PMT used in the first 150 × 150m2 array. This type of PMT has large sensitive area, high quantum efficiency (QE), and large peak-to-valley (P/V) ratio for single photoelectron detection. In this work, we will report on the application of 20 inch MCP-PMT at LHAASO-WCDA.